Rancangan Kerjasama Perpustakaan Sekolah Dalam Memenuhi Kebutuhan Informasi Siswa - Novi Arianti; Yusniah Yusniah; Mirawati Idi Pangestu; Halimah Tusadiah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Libraries are the places where information providers and information seekers are most in demand. Libraries cannot fully meet all the needs of information seekers. To overcome this problem, libraries can collaborate between libraries or more than one library. Collaboration in the library should be planned in advance. With the collaboration of libraries to achieve the same goal, namely to find the information needs of users. There are many types of libraries and one of them is the school library. The school library was created to meet the information needs of the community in the school environment. There are many advantages of cooperating with school libraries, and the most important advantage is that it can meet the information needs of students. This study uses a literatur review taken from sereval jouurnals which are summarized and analyzed. Keywords: collaboration, information, library,